Model of a game-based virtual learning environment to support training processes in organizations (2018)
This thesis presents the definition of a model for the design of virtual learning environments based on games that allow supporting training processes in organizations. For doing so, it starts with a systematic review of literature in order to identify trends in terms of models, approaches, methods, tools, etc., which seek to contribute to the solution of the problems raised in organizational training issues using virtual environments and learning based on games. After this review, a conceptual framework is presented where these two approaches are defined in detail: game-based learning on the one hand, and virtual learning environments on the other. Once defined, the proposed model is presented, specifying its elements and relationships. Finally, the implementation and validation of the model is presented through two real cases, both within a well-known financial entity. In the first case, training is carried out in SCRUM, an agile software development framework, and in the second in SARLAFT (Risk Management System for Money Laundering and Terrorism Financing). Both trainings were later evaluated through surveys, which allow to demonstrate the positive results of the use of the proposed model.